Component unit pricing theory - Cattell, David William (Department of Construction Economics and Management, 2014)
Building contractors are often commissioned using unit price based contracts. They, nevertheless, often compete on the basis of their overall project bids and yet are paid on the basis of these projectsâ constituent item prices. If a contractor decides these prices by way of applying an uneven mark-up to their estimates of their costs, this is known as unbalanced bidding. This research provides proof and explanation that different item pricing scenarios produce different levels of reward for a contractor, whilst exposing them to different degrees of risk. The theory describes the three identified sources of these rewards as well as provides the first explanation of the risks. It has identified the three types of risk involved and provides a model by which both the rewards as well as these risks can now be measured given any item pricing scenario. The research has included a study of the mainstream microeconomic techniques of Modern Portfolio Theory, Value-at-Risk, as well as Cumulative Prospect Theory that are all suited to making decisions that involve trading-off prospective rewards against risk. These techniques are then incorporated into a model that serves to identify the one item pricing combination that will produce the optimum value of utility as will be best suited to a contractorâs risk profile. The research has included the development of software written especially for this purpose in Java so that this theory could be tested on a hypothetical project. A test produced an improvement of more than 150% on the present-value worth of the contractorâs profit from this project, if they apply this model compared to if they instead price the project in a balanced manner.